Platelet-activating factor (PAF-acether) induces high- and low-affinity binding of fibrinogen to human platelets via independent mechanisms. - Kloprogge, E (1986)
When human platelets are incubated with 500 nM-PAF-acether (platelet-activating factor. 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) under equilibrium conditions (60 min, 22 degrees C, non-stirred suspensions), two classes of fibrinogen binding sites are exposed: one class with a high affinity [Kd (7.2 +/- 2.1) X 10(-8) M, 2367 +/- 485 sites/platelet, n = 9] and one class with a low affinity [Kd (5.9 +/- 2.4) X 10(-7) M, 26972 +/- 8267 sites/platelet]. Preincubation with inhibitors of cyclo-oxygenase (acetylsalicylic acid, indomethacin) or thromboxane synthetase (UK 38.485) completely abolishes high-affinity binding, leaving low-affinity binding unchanged. In contrast, ADP scavengers (phosphocreatine/creatine kinase or phosphoenol pyruvate/pyruvate kinase) completely prevent low-affinity binding, leaving high-affinity binding unaltered. Initial binding studies (2-10 min incubation) confirm these findings with a major part of the binding being sensitive to ADP scavengers, a minor part sensitive to indomethacin and complete blockade with both inhibitors. Increasing the temperature to 37 degrees C decreases the number of low affinity-binding sites 6-fold without changing high-affinity binding. Aggregation, measured as the rate of single platelet disappearance, then depends on high-affinity binding at 10 nM-fibrinogen or less, whereas at 100 nM-fibrinogen or more low-affinity binding becomes predominant. These findings point at considerable platelet activation during binding experiments. However, arachidonate metabolism [( 3H]arachidonate mobilization and thromboxane synthesis) and secretion [( 14C]serotonin and beta-thromboglobulin) are about 10% or less of the amounts found under optimal conditions (5 units of thrombin/ml 37 degrees C, stirring). We conclude that PAF-acether induces little platelet activation under binding conditions. The amounts of thromboxane A2 and secreted ADP, however, are sufficient for initiating high- and low-affinity fibrinogen binding via mutually independent mechanisms.